Physical control, transformation and damage in the First World War: War bodies - Delport, Anri (Scientia Militaria - South African Journal of Military Studies, 2021)
Nearly a century after the conclusion of the First World War of 1914–1918, the British military historian Ian FW Beckett expressively stated, “[h]istorians walk with ghosts.”577 As an explanation, he descriptively noted, “[t]hey are privileged … to see what others do not as they tread the deserted banquet-hall of the past, endeavouring to repopulate it with those who have gone before and who might otherwise be forgotten.